A importancia da bioética e do biodireito na sociedade atual - Marchetto, Patricia Borba [UNESP] (My University, 2010)
Considering the dynamics observed in bioethics conceptualization and its projection at the current society, this work, initially, provides a retrospective on the transformation of society over the centuries and, consequently on the emergence of new branches of scientific knowledge. Besides, offers a distinction between law, morality and ethics as a way to make the approximation of a definition of biolaw and bioethics, central theme of this study. Finally, emphasizes the importance of the use of bioethics and biolaw in the solution of conflicts of interest involving the so-called "actuality society law", all aimed at providing better protection for the current society, and particularly to guarantee the protection of fundamental rights for the citizen.

Considerando a dinâmica observada na conceituação da bioética e sua proeminência na sociedade atual, o presente trabalho, inicialmente, realiza uma breve retrospectiva sobre a transformação da sociedade ao longo dos séculos, e, conseqüentemente, sobre o surgimento de novos ramos do conhecimento científico. Diante disso, oferece uma distinção entre direito, moral e ética, como forma de viabilizar a aproximação de uma definição de biodireito e bioética, tema central do presente estudo. Por último, ressalta a importância da utilização da bioética e do biodireito na solução de conflitos de interesses que envolvem os chamados “direitos da atualidade”, tudo isso visando oferecer uma melhor guarida à sociedade atual, e, sobretudo, a garantia de proteção dos direitos fundamentais do cidadão.
Keywords: Interdisciplinarity; Ethics; Moral; Law; Bioethics; Biolaw; Interdisciplinaridade; Ética; Moral; Direito; Bioética; Biodireito